2018
DOI: 10.1055/s-0038-1655763
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of the Anterolateral Ligament of the Knee: A Cadaveric Study

Abstract: Rotational stability of the knee involves not only the cruciate ligaments but also another structure named anterolateral ligament (ALL), the function of which is still controversial. This study evaluated the effectiveness of high-resolution ultrasound (US) examination to detect the ALL. We studied 8 cadaveric knees (8 ALLs). On each knee, high-resolution real-time ultrasonography examination was performed by an experienced musculoskeletal radiologist before and after the procedure, with the surgeons blind to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The authors reported that the ALL could be identified as a distinct, distinguishable structure in all 10 specimens using the MRI [ 17 ]. In another cadaver study, Zappia et al performed a high resolution, real time ultrasonography evaluation of the ALL in eight specimens [ 20 ]; the results of the latter study showed that the ALL was distinguished in all eight cadaver limbs, and that the ultrasound examination was a useful tool to investigate the ALL features and its injuries.…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported that the ALL could be identified as a distinct, distinguishable structure in all 10 specimens using the MRI [ 17 ]. In another cadaver study, Zappia et al performed a high resolution, real time ultrasonography evaluation of the ALL in eight specimens [ 20 ]; the results of the latter study showed that the ALL was distinguished in all eight cadaver limbs, and that the ultrasound examination was a useful tool to investigate the ALL features and its injuries.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the US is an adequate tool for identifying the ligament. Likewise, Zappia et al 20 in an anatomical study with cadavers concluded that ultrasound is useful for assessing ALL but emphasized the importance of studies evaluating its visualization in the knees of patients with ACL injuries.…”
Section: Discussionmentioning
confidence: 99%
“…All US examinations were performed to detect the anatomical landmarks (Gerdy’s tubercle, Lateral collateral ligament (LCL), iliotibial band, popliteus tendon, and ALL) with the knee flexed at 10° and 10° of internal rotation to give some tension to the ALL. Thus, the ALL was first assessed distally by identifying Gerdy’s tubercle and looking for a ligamentous structure beginning posterior to the tubercle with directionality pointing toward the footprint of the LCL on the lateral femoral condyle, as described in literature [ 41 ].…”
Section: Methodsmentioning
confidence: 99%